Orientation-dependent chord length distribution in a convex quadrilateral - Martirosyan, D. M. (Հայաստանի ԳԱԱ)
This work contributes to the research devoted to the recognition of a convex body by probabilistic characteristics of its lower-dimensional sections. In this paper, for any convex quadrilateral, five orientation-dependent characteristics are introduced and explicitly evaluated per direction. In terms of these characteristics, simple explicit representations of the orientationdependent chord length distribution function and the covariogram are obtained not only for an arbitrary convex quadrilateral but also for any right prism based on it.
Keywords: Mathematics